"Giving voice to the voiceless": An exploration of the grieving ritual for a therapy dog. Issue 3 (16th March 2023) - Mc Veigh, Mary Jo
Abstract: The use of animal-assisted therapy with children who have experienced trauma is receiving increasing attention in the literature. However, there is a lack of attention given to the death of therapy animals. The scholarship on the death of animal companions highlights a varying depth of acknowledgment of children's grief. This article draws on the clinical experience of one therapy center's approach to the death of a therapy dog. Knowledge gained from this experience highlighted the necessity of acknowledging the death, the need for clear communication with children and young people, and the importance of involving children in a memorial ritual.